Determinación de linfocitos T CD4, CD8 y Tγδ en la infección experimental con Brucella ovis - Sánchez-Parra, Víctor Manuel (2019)
The objective of this study was to determine the blood distribution of CD4, CD8, and T γδ lymphocytes (WC1) in rams experimentally infected with Brucella ovis. Eighteen rams from 1 to 4 years old and free from B. ovis were distributed in three groups: Control (n=6); Inoculated in the ocular and preputial mucosa (n=6); Inoculated intravenously (n=6). Serological follow-up was carried out from the day of inoculation until 189 dPI (post-inoculation day). CD4 and CD8 lymphocyte populations were immunotyped at 120, 150 and 189 and WC1 (Tγδ lymphocytes) at 120 dPI by flow cytometry. The rams, from the third dIP began to seroconvert; at 21 and 28 dPI all animals of the inoculated intravenously and in the mucosa groups, respectively, were positive; likewise, 50% of the animals of the challenged groups were presented as positive or suspect to the ELISA test at 189 dPI. Differences were found in the Mean Fluorescence Intensity (MFI) of the CD8 lymphocytes between the control group (1027.4) and the group inoculated intravenously (499.6) at 120 dPI (p<0.05) and in the MFI of the lymphocytes CD4 between groups at 189 dPI (p<0.05). The T γδ lymphocyte populations (WC1) presented differences in MFI between the control group and the groups inoculated at 120 dPI (p<0.05). The results indicated that B. ovis can modulate host immune response, that CD4 and CD8 lymphocytes are important for host defence against this infection, and that populations of CD4 and CD8 can fluctuate during the period of B. ovis infection. Besides, the participation of T γδ lymphocytes could be an important factor in the control of the infection caused by B. ovis.